Problems of Learning Maharah Kalam in Arabic Language Learning for Students of MTs EX-PGA Univa Medan - Jabat, Yuyun Jelita; Taufiq, Muhammad (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This study explains and describes the problems faced in learning Arabic, particularly in speaking skills. Arabic is a second language learned by students at school, and as such, many students face difficulties when practicing speaking skills. The writing method used in this article involves library research as well as field observations through interviews with teachers, students, and direct observation, in order to obtain the expected research results. The purpose of this study is to explore more deeply the factors that influence students in practicing Arabic speaking skills and to identify possible solutions to those difficulties. The findings of the research reveal several factors that contribute to students' difficulties in speaking Arabic. These include a lack of vocabulary (mufrodat), diverse educational backgrounds or previous schooling, an unsupportive language environment that hinders the development of Arabic-speaking situations, and low motivation and interest in learning among students. To address this problem, the school should create a supportive Arabic-speaking environment as an effective step to improve students’ speaking skills, because through positive reinforcement and habituation, students will become more motivated